2017
DOI: 10.1016/j.eatbeh.2017.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Are perfectionistic concerns an antecedent of or a consequence of binge eating, or both? A short-term four-wave longitudinal study of undergraduate women

Abstract: The perfectionism model of binge eating (PMOBE) posits perfectionistic concerns are a vulnerability factor for binge eating. And evidence indicates perfectionistic concerns and binge eating correlate positively. Yet the direction of this relationship is unclear. In particular, it is unclear if perfectionistic concerns represent an antecedent of binge eating (a vulnerability effect with perfectionistic concerns predicting increases in binge eating), a consequence of binge eating (a complication effect with bing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 21 publications
0
13
0
1
Order By: Relevance
“…Although these two aspects of clinical perfectionism conceptually correspond to the two higher order perfectionism constructs of personal standards and evaluative concerns, respectively (e.g., Dunkley et al, 2006;Stoeber & Damian, 2014), Shafran and colleagues (2002) conceptualized clinical perfectionism as a unidimensional construct. We contend that, akin to the notion that perfectionism is a single general factor (e.g., Egan et al, 2016;Smith & Saklofske, 2017), clinical perfectionism is best understood as a single factor that reflects an overreaching desire to meet high standards and self-criticism in response to failing to meet those standards.…”
Section: Perfectionism and Disordered Gamblingmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these two aspects of clinical perfectionism conceptually correspond to the two higher order perfectionism constructs of personal standards and evaluative concerns, respectively (e.g., Dunkley et al, 2006;Stoeber & Damian, 2014), Shafran and colleagues (2002) conceptualized clinical perfectionism as a unidimensional construct. We contend that, akin to the notion that perfectionism is a single general factor (e.g., Egan et al, 2016;Smith & Saklofske, 2017), clinical perfectionism is best understood as a single factor that reflects an overreaching desire to meet high standards and self-criticism in response to failing to meet those standards.…”
Section: Perfectionism and Disordered Gamblingmentioning
confidence: 99%
“…More recently, though, evidence has emerged in favour of the unidimensional camp. Specifically, Smith and Saklofske (2017) showed that these higher order dimensions reflect a single general perfectionism factor. In the current paper, for parsimony, we adhere to Smith and Saklofske's understanding of perfectionism as a single general factor.…”
Section: Perfectionism and Disordered Gamblingmentioning
confidence: 99%
“…Longitudinal research also supports the links with bulimic (Kehayes, Smith, Sherry, Vidovic & Saklofske, 2019) and binge eating behaviours (Smith et al, 2017). Recent research has indicated that perfectionism may mediate the link between other antecedents to disordered eating, such as social interaction anxiety (Menatti, Weeks, Levinson, & McGowan, 2013), rumination (Riviere & Douilliez, 2017), and social appearance anxiety .…”
Section: Introductionmentioning
confidence: 85%
“…By contrast, while Hewitt and Flett (1991) directly link with eating disorder symptoms in cross-sectional analyses (Hewitt et al, 1995) and longitudinal analyses (Smith et al, 2017;Soares, Macedo, et al, 2009), the evidence for…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation